2017
DOI: 10.1111/jac.12200
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards flowering of faba bean (Vicia faba L.) is more than photothermal

Abstract: Predicting and understanding the progress towards flowering in faba bean are important to achieve the adaptation and high productivity of the crop under varying environmental conditions. Traditional controlled-environment experiments showed that the rate of progress towards flowering was dependent mainly on photoperiod and temperature. Here, we highlight the need to include measures of solar radiation and water deficit in order to achieve an adequate model for field conditions. The improved model was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
(70 reference statements)
0
15
0
Order By: Relevance
“…The application of exogenous cytokinin may compensate for this reduction. sponse progression needs to be addressed (e.g., Croser et al, 2018;Lizarazo et al, 2017). Combinations of SB protocols involving plant growth regulators and light modification were used to optimize early flowering response that lead to acceleration of generation advance in other pulse crops (Mobini et al, 2015;Mobini & Warkentin, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of exogenous cytokinin may compensate for this reduction. sponse progression needs to be addressed (e.g., Croser et al, 2018;Lizarazo et al, 2017). Combinations of SB protocols involving plant growth regulators and light modification were used to optimize early flowering response that lead to acceleration of generation advance in other pulse crops (Mobini et al, 2015;Mobini & Warkentin, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These approaches, combined with results here, may lead to additional reduction in faba bean generation time as part of a reliable speed breeding protocol for this species. Lizarazo et al (2017) showed that progression towards flower development in faba bean was affected not only by photoperiod and temperature but also by abiotic stress and solar radiation. In addition, novel ways of achieving earliness, such as deployment of the terminal-inflorescence mutation (ti), may provide complementary additions to the protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, low light quality (Mobini et al, 2016;Yuan et al, 2017) or water stress (Gorim & Vandenberg, 2017) can accelerate flowering, while supraoptimal temperatures will delay and/or prevent flowering (Saint-Clair, 1972;Summerfield et al, 1991). Lizarazo et al (2017) were able to improve their DTF predictions in faba bean with the inclusion of solar radiation and water deficit measures to the photothermal model. In Metaponto, Italy 2017, 126 of the 181 days of the field trial had a daily mean temperature below 15°C and experienced mean temperatures of less than 5°C on the 90-93 rd and 115 th day after sowing (Fig.…”
Section: Dtf Can Be Modeled Using Mean Temperature and Photoperiodmentioning
confidence: 99%
“…; Ellis et al, 1994a), mung bean (Vigna spp. ; Ellis et al, 1994c) and faba bean (Vicia faba L.; Catt & Paull, 2017;Lizarazo et al, 2017); and has potential utility for predicting days from sowing to flowering and quantifying temperature and photoperiod sensitivity, which could assist breeders in identifying genotypes adapted to a specific environment. In addition, equation 1 can be modified to estimate the 'nominal base temperature'…”
Section: Introductionmentioning
confidence: 99%